Laser micro drilling of 316L stainless steel orthopedic implant: A study. (April 2020) - Pattanayak, S.; Panda, S.; Dhupal, D.
Graphical abstract: Highlights: Laser micro drilling on an orthopedic implant is performed with argon assist gas to improve drilled hole quality for better fixing the implants. Key process parameters that controls different quality features of drilled hole are identified. GRA and GRA-COV were applied for analysis of experimental results. To establish the difference between these two statistical approaches in a meaningful way, some statistical significance tests are performed. An attempt has been made in this study to control the heat affected zone, recast layer thickness, hole circularity and hole taper angle. Abstract: It has recently been shown that there is a requirement of inclined micro hole with smooth side walls (without cracks and burr), high aspect ratio, low taper, reduced heat affected zone (HAZ) and thin recast layer on orthopedic implant. So with the aim of improving hole quality characteristics and functionality of implant a multi-objective optimization of laser micro drilling with argon as an assist gas is addressed in this study. A hybrid statistical approach based on grey relational analysis (GRA) and coefficient of variation (COV) is proposed to analyse the experimental data. The key process variables responsible for quality improvement are identified. Four statistical tests are performed to compare the hybrid and GRA approach. Further, it was found that the proposed hybrid is more superior to GRA in terms of computational time and ease of computation. It is also observed that focal point position and diode current have striking effect of hole quality. An important implication of this paper is that thin recast layer, small HAZ width and spatter area were observed, when argon was used as an assist gas.